2010
DOI: 10.1093/sleep/33.9.1159
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia with Short Sleep Duration and Mortality: The Penn State Cohort

Abstract: Insomnia with objective short sleep duration in men is associated with increased mortality, a risk that has been underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
271
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 355 publications
(291 citation statements)
references
References 31 publications
14
271
2
4
Order By: Relevance
“…8 Unfortunately, we could not statistically adjust for hypertension or diabetes; thus, our results cannot provide a clear explanation for the high mortality rate of the insomnia group. 10,11,21 However, a previous study that objectively defined insomnia using PSG indicated that short sleep duration is associated with a higher mortality rate, 21 which partially supports our results.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…8 Unfortunately, we could not statistically adjust for hypertension or diabetes; thus, our results cannot provide a clear explanation for the high mortality rate of the insomnia group. 10,11,21 However, a previous study that objectively defined insomnia using PSG indicated that short sleep duration is associated with a higher mortality rate, 21 which partially supports our results.…”
Section: Discussionsupporting
confidence: 89%
“…35 Until now, there have been inconsistent findings across studies about the relationship between insomnia and mortality. 21,25,36,37 The SMRs of the insomnia group and the KaplanMeier survival curve analyses showed that insomnia was a risk factor for increased all-cause mortality compared to the no-sleep-disorder group. According to Cox regression analyses, the risk of cardiovascular mortality in the insomnia group was 8.11 times higher even after adjusting for age and sex, and the Kaplan-Meier curve showed that the survival rate of the insomnia group was significantly lower than that of the no-sleep-disorder group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…이에리쟈 · 이금재 사회생활 등 일상생활의 많은 영역에 영향을 미치며, 집중력 과 기억력의 저하를 유발하는 원인이 되며 (Ohayon, 2011), 불면증과 같은 수면장애가 만성적으로 나타날 경우 고혈압과 2형 당뇨병 등 의학적 질병 발생과 사망 위험이 증가되므로 (Vgontzas et al, 2010), 최적의 건강상태를 유지하기 위해서 는 수면의 질 관리는 필수적이다.…”
unclassified